Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1039/c7ta10762e
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced electrochemical response of Sr(Ti0.3Fe0.7Ru0.07)O3−δ anodes due to exsolved Ru–Fe nanoparticles

Abstract: The performance of an anode for solid oxide fuel cells, a mixed conducting oxide SrTi0.3Fe0.7O3−δ (STF), is improved by Ru0.8Fe0.2 nanoparticles formed by ex-solution, which promote the hydrogen adsorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 31 publications
(64 reference statements)
1
25
0
Order By: Relevance
“…Interestingly, noble metals can be paired with base metals like Ni and Fe mainly, in order to boost the catalytic activity of base metals [6e, 31] . Pt−Ni alloy (Pt 3 Ni) nanoparticles were exsolved from La 0.9 Mn 0.9 Pt 0.075 Ni 0.025 O 3‐δ and the newly exsolved material exhibited enhanced activity for oxygen reduction reaction (ORR) comparable to that of the commercial catalyst Pt/C, but also higher stability over Pt/C.…”
Section: Bimetallic Alloy Nanoparticle Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, noble metals can be paired with base metals like Ni and Fe mainly, in order to boost the catalytic activity of base metals [6e, 31] . Pt−Ni alloy (Pt 3 Ni) nanoparticles were exsolved from La 0.9 Mn 0.9 Pt 0.075 Ni 0.025 O 3‐δ and the newly exsolved material exhibited enhanced activity for oxygen reduction reaction (ORR) comparable to that of the commercial catalyst Pt/C, but also higher stability over Pt/C.…”
Section: Bimetallic Alloy Nanoparticle Systemsmentioning
confidence: 99%
“…Additionally, Ru−Fe alloy nanoparticles were reported to exsolve from a Sr(Ti 0.3 Fe 0.7 Ru 0.07 )O 3‐δ in a SOFC anode resulting in lower polarization resistance and higher maximum power density especially at low temperatures and hydrogen partial pressures, as compared to the cell using the Ru‐free perovskite anode. This was attributed to the promoting effect of the exsolved Ru−Fe nanoparticles on hydrogen adsorption which was the rate limiting step for the Ru‐free anode [31] …”
Section: Bimetallic Alloy Nanoparticle Systemsmentioning
confidence: 99%
“…Furthermore, defect rich perovskites used as anodes are mixed ion-electron conductors, which is immensely beneficial for this kind of application. Examples of utilized systems are Sr 0.95 (Ti 0.3 Fe 0.63 Ni 0.07 )O 3-δ , where exsolution of Ni 0.5 Fe 0.5 nanoparticles could be observed [32], or Sr(Ti 0.3 Fe 0.7 Ru 0.07 )O 3-δ , where Ru 1-x Fe x particles were found [33]. In both cases, exsolved particles significantly reduced anode polarization resistance.…”
Section: Applicationsmentioning
confidence: 99%
“…Several studies have already shown that the performance of established SOFC electrodes can be improved by doping with additional catalytically active elements. For example, studies on SrTi x Fe 1− x O 3− δ revealed positive effects of Co, 70 Ni 71,72 or Ru 73 doping on the polarisation resistance of the electrode and showed increased long term stability. Similar effects were found on La 1− x Sr x CrO 3− δ after doping with Ru or Ni.…”
Section: Introductionmentioning
confidence: 99%